Forging Transnational Connections: The Role of the UNRA University and the Baltic University shaping Potwar Educational Landscapes - Pakštalis, Arvydas; Tranavičiūtė, Brigita (Historia y Memoria de la Educación, 2025)
This article aims to address a gap in the historiography of the higher education of displaced persons (DPs) by analysing the efforts of forced migrants from the Baltic States to reconstruct higher education in exile. It focuses on the establishment and evolution of the UNRRA University and the Baltic University, two significant educational institutions created for DPs in postwar Europe. Through a comparative analysis, the study underscores the role of education in shaping transnational identities and addresses the complexities of establishing educational spaces for DPs in the postwar context It explores how the concepts of transnationality and transculturality were reflected in the UNRRA and Baltic universities as displaced persons sought to implement these ideas by drawing on their national educational traditions while navigating cultural differences. The UNRRA University was founded in Munich in 1945 by professors and students mainly from Soviet-occupied countries, aiming to foster international cooperation and revitalise humanism among a diverse, multilingual student body. Despite initial success, shifting Allied priorities led to its eventual dissolution in 1947, highlighting the fragility of transnational educational initiatives in politically charged environments. The Baltic University was conceived by Lithuanian, Latvian, and Estonian refugees seeking to maintain their cultural identities and academic pursuits. Established in 1946, it aimed to unite the three Baltic nations in their quest for higher education while navigating challenges posed by nationalistic tendencies and external pressures from authorities. Although the Baltic University fostered collaboration, it ultimately faced instability due to competing interests and changing administrative directives.